Spontaneous Brain Oscillations and Perceptual Decision-Making. Issue 8 (August 2020) - Samaha, Jason; Iemi, Luca; Haegens, Saskia; Busch, Niko A.
Abstract : Making rapid decisions on the basis of sensory information is essential to everyday behaviors. Why, then, are perceptual decisions so variable despite unchanging inputs? Spontaneous neural oscillations have emerged as a key predictor of trial-to-trial perceptual variability. New work casting these effects in the framework of models of perceptual decision-making has driven novel insight into how the amplitude of spontaneous oscillations impact decision-making. This synthesis reveals that the amplitude of ongoing low-frequency oscillations (<30 Hz), particularly in the alpha-band (8–13 Hz), bias sensory responses and change conscious perception but not, surprisingly, the underlying sensitivity of perception. A key model-based insight is that various decision thresholds do not adapt to alpha-related changes in sensory activity, demonstrating a seeming suboptimality of decision mechanisms in tracking endogenous changes in sensory responses. Highlights: Spontaneous changes in low-frequency oscillatory amplitude bias moment-to-moment perceptual decisions through criterion effects, not sensitivity changes. Models of perceptual decision-making combined with neurophysiological evidence suggest that spontaneous alpha-band oscillations modulate sensory responses without changing the fidelity of stimulus representations. Criteria underlying subjective measures of perception, such as detection, visibility, and confidence, do not adapt to alpha-related changes in sensory processing, leading to dissociations between objective and subjective aspects of perception. There is emerging support for a domain-general effect of alpha on perceptual decisions across sensory modalities.